Implementation Challenges of the New Criminal Code for Victim Protection: A Restorative Justice Perspective - Raden Azhari Setiadi; David Bani Adam; Nur Baiti Rahman; Muhammad Ruslan Afandi (Journal of Law, Human Rights, Immigration, and Corrections, 2026)
The implementation of the new Criminal Code (KUHP) in Indonesia presents major challenges in protecting crime victims, especially due to regulatory inconsistencies, disharmony among law enforcement agencies, and limited understanding of Restorative Justice principles. This study analyzes both normative and empirical aspects while offering more humanistic, restorative justice-based solutions. The research method is normative juridical, using statutory and case approaches. Findings indicate that regulatory harmonization, active involvement of victims and the community, strengthening judges’ roles, and improving education and capacity building for relevant institutions are key steps for optimizing victim protection. Additionally, developing technical guidelines for Restorative Justice implementation and increasing synergy law enforcement main recommendations. Empowering victims with information access and psychological support is also essential for optimal recovery. The conclusion emphasizes need for comprehensive, cross-sectoral collaboration and ongoing evaluation to ensure effective, fair, and truly victim-oriented application of Restorative Justice in the era of the new Criminal Code.